Evaluation of functional magnetic resonance imaging in the identification of presurgical epileptic zones comparison between conventional and advanced techniques in patients with drug-refractory epilepsy: a systematic review - Santiago, Luisana Darionara Maldonado De; Jiménez, Maria Luisa Guerrero; Quilligana, Jennifer Marisol Cayambe; Miranda, Dario Javier Caguate; Sola, Iveth Melissa Valencia; Calderon, John Jairo Salgado; Silva, Andrea Blanco; Vasquez, Elias David Suarez (International Journal of Research in Medical Sciences, 2025)
Drug-refractory epilepsy (DRE) is a significant clinical challenge when conventional treatments are ineffective. Localization of epileptic zones is essential for successful surgery but conventional techniques such as scalp EEG, PET and structural MRI are usually ineffective, particularly in MRI-negative cases. Functional MRI (fMRI) has emerged as a valuable tool for presurgical assessment by offering information on seizure networks and functional connectivity. This systematic review evaluates the efficacy of traditional and novel fMRI methods in identifying epileptogenic areas and enhancing surgical outcomes. Traditional fMRI with task-based paradigms assists in mapping cerebral functions but is constrained by patient compliance and inability to detect deeply seated foci. Novel techniques like resting-state fMRI (rs-fMRI) EEG-fMRI fusion and analysis aided by AI provide greater spatial and temporal resolution for better epileptic network localisation. These methods are of use for MRI-negative patients and those patients with motor or cognitive deficits. Advanced fMRI techniques, though, require a lot of computational power and skill which can limit their application. Through consideration of the literature, this paper indicates the advantages and limitations of each technique and emphasizes the value of the integration of multiple methods to enhance presurgical planning. The results indicate that improved fMRI techniques have the potential to increase the success of surgery and enhance patients’ quality of life with DRE. The research should further improve these techniques so that they are more accessible and feasible for use in clinics.